Molecularly imprinted polypyrrole-modified screen-printed electrode: Toward a sensor for furfural derivatives determination - Daniele Merli; Alessandra Cutaia; Sofia Prosperi; Camilla Zanoni; Giancarla Alberti (Sensors and Actuators Reports)
The increasing interest in determining furfural derivatives in food and beverages using low-cost and portable devices has driven our attention to the development of the here proposed voltammetric sensor. It is based on a screen-printed electrochemical cell whose graphite-ink working electrode is surface modified with electropolymerized molecularly imprinted polypyrrole (e-MIP), using 5-(hydroxymethyl)furan-2-carbaldehyde (HMF) as the template. Square wave voltammetry (SWV) is the selected analytical technique, exploiting the irreversible reduction peak of the carbonyl group at -1.7 V vs. Ag/AgCl pseudo reference electrode in 0.1 M phosphate buffer (PBS) at pH 8. The presence of the e-MIP on the working electrode surface enhances the sensitivity by lowering the detection limit of about one order of magnitude if compared with the bare electrode (LOD bare 93 µM; e-MIP 7 µM). The developed sensor is selective for the whole class of furfural-like compounds, allowing the determination of the total furanic aldehydes content. The sensor was applied to the analysis of synthetic solutions and real beverages, such as expresso coffee, obtaining good recovery percentages.